Atg16L1 deficiency confers protection from uropathogenic Escherichia coli infection in vivo - Wang, Caihong; Mendonsa, Graziella R; Symington, Jane W; Zhang, Qunyuan; Cadwell, Ken; Virgin, Herbert W; Mysorekar, Indira U (Proceedings of the National Academy of Sciences - PNAS, 2012)
Urinary tract infection (UTI), a frequent and important disease in humans, is primarily caused by uropathogenic Escherichia coli (UPEC). UPEC forms acute cytoplasmic biofilms within superficial urothelial cells and can persist by establishing membrane-enclosed latent reservoirs to seed recurrent UTI. The host responds with an influx of innate immune cells and shedding of infected epithelial cells. The autophagy gene ATG16L1 has a commonly occurring mutation that is associated with inflammatory disease and intestinal cell abnormalities in mice and humans. Here, we show that Atg16L1-deficient mice (Atg16L1 ᴴᴹ) cleared bacteriuria more rapidly and thoroughly than controls and showed rapid epithelial recovery. Atg16L1 deficiency was associated with a potent proinflammatory cytokine response with increased recruitment of monocytes and neutrophils to infected bladders. Chimeric and genetic studies showed that Atg16L1 ᴴᴹ hematopoietic cells alone could increase clearance and that Atg16L1-deficient innate immune cells were required and sufficient for enhanced bacteriuric clearance. We also show that Atg16L1-deficient mice exhibit cell-autonomous architectural aberrations of superficial urothelial cells, including increases in multivesicular bodies, lysosomes, and expression of the UPEC receptor Up1a. Finally, we show that Atg16L1 ᴴᴹ epithelial cells contained a significantly reduced number of latent reservoirs. Together, our results show that Atg16L1 deficiency confers protection in vivo to the host against both acute and latent UPEC infection, suggest that deficiency in a key autophagy protein can be protective against infection in an animal model of one of the most common diseases of women worldwide, and may have significant clinical implications for understanding the etiology of recurrent UTIs.